Community Management of Water: the Case of Umbeluzi Basin, Mozambique - Chilundo, Eduardo; Tembe, Joel Das Neves (Water Nepal, 2003)
Access to water resources and the efficient and equitable use of water have become two of the most critical aspects of government policy and community development around the world. The Mozambican government, for example, is now engaged in the development of water policy and management. The analysis of local people’s water management practices, their perceptions of water management institutions and the implications of public policy for the rural water supply system in the Umbeluzi Basin of Mozambique is the main concern of this paper. Economic activity in the communities of the Umbeluzi basin is based on both rainfed and irrigated agriculture and on animal husbandry. The area is served by three different water systems: piped water for domestic use; water for irrigation purposes; and, also to meet domestic needs, public drinking fountains supplied by boreholes and equipped with electrical pumps (i.e. standpipes). Under the current water rights system, water drawn from rivers is free, whereas water stored in dams built by the government or water pumped directly from rivers is sold at a uniform price throughout the country. This price is set so that only operation and maintenance costs are recovered; capital costs are not. Likewise, drinking water from standpipes is priced to recover only operation and maintenance costs. The overall strategy is to ensure that access to water for multiple uses (drinking, irrigation, etc.) is defined by the government. An integrated approach to planning and implementation, based on the principles of sustainable development, is now being implemented through a series of reforms.Water Nepal Vol.9-10, No.1-2, 2003, pp.369-378